Analisis Maqāṣid Syarī‘ah terhadap Pertimbangan Hakim dalam Putusan Nafkah Anak Pasca Perceraian di Pengadilan Agama: An Analysis of the Maqāṣid al-Sharī‘ah in Relation to Judges' Considerations in Post-Divorce Child Support Rulings in Religious Courts - Nur Afifa Maharani; Kurniati; Zulhas’ari Mustafa (Sekolah Tinggi Agama Islam Negeri Majene, 2026)
This study examines how maqāṣid syarī‘ah are applied in judicial reasoning on child maintenance after divorce and how they support the protection of children's rights. Using the framework of al-kulliyyāt al-khams, namely the preservation of religion, life, intellect, lineage, and property, the study assesses whether religious court decisions place children's welfare at the center of legal consideration. The research uses a normative legal method, drawing on statutory and case law. It compares three decisions: Decision Number 2487/Pdt.G/2024/PA.Mks, Decision Number 1800/Pdt.G/2024/PA.Pas, and Decision Number 147/Pdt.G/2025/PA.Gtlo. The analysis uses content and comparative analysis to examine the five main objectives of Islamic law. The findings show a shift from formal legal reasoning toward substantive justice in child maintenance cases. The dominant maqāṣid dimensions are ḥifẓ al-nafs, ḥifẓ al-‘aql, and ḥifẓ al-nasl. These include protecting children's basic needs, education, psychological well-being, and continued parental responsibility after divorce. Each decision shows a different pattern. Decision No. 2487/Pdt.G/2024/PA.Mks emphasizes psychological protection and the quality of caregiving. Decision No. 1800/Pdt.G/2024/PA.Pas prioritizes education and living needs based on the father's stable income. Decision No. 147/Pdt.G/2025/PA.Gtlo balances children's needs with the father's financial capacity and regional living costs. However, maintenance awards still rely mainly on the father's financial ability rather than on objectively measured child needs. The study recommends measurable child maintenance guidelines based on age, education, healthcare, living costs, and verified parental income.